Anatomía patológica y patogenia de los bocios - Bianchi, Andrés E. (1937)
The author thinks that the classification of the goitres made by Wolfier fifty years ago can be seen again with success. Effectually, to-day we know the chemical value and the reactive character of the benign goitres; facts unknowm by this author. In consequence the Brioty forms must not be considered like adenomes but ou the contrary as knoty hyperplasies as Virchow indicated many years ago. According to the demonstration made by Marine and his school, the basic cause of the goitres seems to be a deficit of the iodine contained in the thyroid gland, a deficit due to a diminution in the food as well as to a strange condition of the thyroid gland's work, which for Basedow's disease can be a strange sympathetic excitation. Refused the adenomatose nature of the thyroid knots and established the relation between the Basedow's disease and the others benign goitres the reason to sustain a dualistic concept and classification disappears. It is possible to indicate histological characteristic aspects for each of goitres, included the Basedow's struma and also to study the relations between the different types of this disease. According to these facts it appears the great importance that the iodine has in the struggle against the goitres and the diseases connected with them for example: the malignant thyroid gland's tumours.